DOZ047.65: Radiofrequency ablation: a promising treatment in children with early onset Barrett's esophagus. (24th June 2019) - Rea, F; Isoldi, S; Accarpio, F; Baldi, F; Giulia, A; Romeo, E; Faraci, S; Contini, A; Tambucci, R; Balassone, V; Caldaro, T; Dall'Oglio, L; et al.
Abstract: Aim of the Study: Barrett's esophagus (BE) could be a rare late complication in children with repaired esophageal atresia, partly due to a long-term history of gastro-esophageal reflux disease (GERD). Radiofrequency ablation (RFA) is the best endoscopic technique in adults with BE and dysplasia. Guidelines do not support this approach for non-dysplastic BE. Aim of this study is to present our experience as Tertiary Gastroenterology referral Centers in the treatment of children and young adults with BE using RFA. Methods: A multicenter retrospective study conducted on children with BE, subjected to RFA at the Digestive Surgery and Endoscopy Unit, Bambino Gesù Children's Hospital and the Department of General Surgery 'Paride Stefanini', Sapienza University of Rome, between June 2012 and December 2017.Demographic and clinical data were collected. BE characteristics according to Prague classification, presence and grade of dysplasia, number of RFA treatments, complications, clinic and endoscopic outcomes were described. All patients were treated with HALO RF BARRX tm (HALO 360 Covidien, Sunnyvale, California, USA). Endoscopic evaluation and treatment were performed every 3 months until complete eradication. Endoscopic follow-up was: 6 months after eradication, and then annually. Results: Five patients were evaluated (M:5). Mean age at diagnosis was 14.4 years (range: 9–17); mean age at first treatment was 23 years (range: 13–36). Two patients presented with repaired esophageal atresia (long gap, type 3 atresia), 3 with peptic strictures. All patients exhibited a long-term history of symptomatic GERD and PPI dependency. Four patients underwent Nissen fundoplication before BE diagnosis. All patients presented with long segment BE (mean baseline length was 8, 8 cm, range 7–10 cm). According to the Prague classification, patients were classified as follows: C0M7, C0M17, C8M10, C0M9 and C4M8. One patient presented with LGD. Patients received a mean of 3 HALO treatments (range 1–4 sessions). Eradication was 100% during 2- to 6-year follow-up (mean 4.5 year). No complications occurred. Conclusions: Pediatric patients with EA present an high risk to develop early BE, therefore endoscopic surveillance is mandatory. RFA represents a safe and effective treatment option in patients with early onset BE. Treatment of BE with this technique could be a useful and minimal invasive strategy for dysplasia and cancer prevention.